Critical Discourse Analysis of News Coverage on The Hoisting of The One Piece Flag In Online Media Tempo.CO and CNN Indonesia.com - Chaidar Irfan (Universitas Muria Kudus, 2026)
This study aims to analyze the discourse construction of news coverage regarding the hoisting of the One Piece flag in Tempo.co and CNNIndonesia.com. This phenomenon is understood not merely as an expression of popular culture, but also as a symbol that generates public debate concerning nationalism, freedom of expression, and the relationship between the state and civil society. This research employs a qualitative approach within a critical paradigm, utilizing Teun A. van Dijk's Critical Discourse Analysis model, which encompasses three interrelated dimensions: textual structure, social cognition, and social context. The data consist of two news texts published in August 2025: “Problematika Pengibaran Bendera One Piece” from Tempo.co and “Wamendagri Sebut Fenomena Bendera One Piece Bagian dari Ekspresi Warga” from CNNIndonesia.com. The findings reveal that Tempo.co tends to frame the phenomenon as a symbol of social criticism rooted in public dissatisfaction, while CNNIndonesia.com presents it as a form of civic expression that remains bounded by state symbolism and constitutional norms. These findings confirm that media institutions are not neutral actors; rather, they actively construct the social and political meaning of events through language, source selection, and ideological positioning.